MATURITY STAGES AND PACKAGING PERFORATIONS AFFECT THE QUALITY OF PLUM IN COLD STORAGE - A. Rab; F. Ahmad; M. Ahmad; S. T. Shah (Journal of Animal and Plant Sciences, 2016)
The influence of maturity stages (pale green, yellow and purple) and package perforations (0, 5, 10, 15, 20 and 25) was investigated on the quality of plum fruit during storage (25 days) at low temperature (5±2 °C). The fruit quality was significantly affected by maturity stages (MS), packing perforation (PP) and storage duration (SD) as well as the MS x SD and PP x SD interactions. After 25 days storage, the fruits harvested at pale green stage had the lowest weight loss (1.81%) and disease incidence (3.71%), which increased to the highest 2.28% and 17.61%, respectively in fruits harvested at purple stage of maturity. In PP x SD interaction, the weight loss (5.23%) and disease incidence (18.58%), after 25 days storage were maximum in 0 package perforations and the least 1.24% and 1.86% respectively with 15 package perforations. The MS x SD interaction resulted in maximum fruit firmness (4.81 kg cm-2) and titratable acidity (1.11%), in fruits harvested at pale green stage that decreased to 3.78 kg cm-2 and 0.92% in fruits harvested at purple stage. Similarly, storage of fruits for 25 days resulted in significantly lower fruit firmness and titratable acidity as compared to corresponding values at each maturity stages. By contrast, the least TSS (7.58%), TSS/Acid ratio (6.18) and Ascorbic acid (5.78 mg 100 g-1) was recorded at pale green stage increased to the maximum of 12.78%, 13.89 and 6.99 mg 100g-1, respectively at purple stage. In PP x SD interaction the range of fruit firmness (4.36-4.38 kg cm-2), acidity (1.001 to 1.005%) and Ascorbic acid (6.18 to 6.39 mg 100g-1) at day 0, decreased at each level of package perforations, with the highest fruit firmness (2.57 kg cm-2), acidity (0.735%) and Ascorbic acid (5.78 mg 100g-1) recorded in fruits stored with 15 packages perforation. Plum fruits harvested at pale green stage packed in 15 perforation packages proved the best in retaining most of the quality attributes during storage.
Keywords: Fruit quality attributes maturity stages; perforation packages; plum; shelf life